Fetal Liver Volume Assessment Using Magnetic Resonance Imaging in Fetuses With Cytomegalovirus Infection† - Hawkins-Villarreal, Ameth; Moreno-Espinosa, Ana L.; Martinez-Portilla, Raigam J.; Castillo, Karen; Hahner, Nadine; Nakaki, Ayako; Trigo, Lucas; Picone, Olivier; Siauve, Nathalie; Figueras, Francesc; Nadal, Alfons; Eixarch, Elisenda; et al. (Frontiers in Medicine, 2022)
Objective: To assess fetal liver volume (FLV) by magnetic resonance imaging (MRI) in cytomegalovirus (CMV)-infected fetuses compared to a group of healthy fetuses. Method: Fetuses were considered severely or mildly affected according to prenatal brain lesions identified by ultrasound (US)/MRI. We assessed FLV, the FLV to abdominal circumference (AC) ratio (FLV/AC-ratio), and the FLV to fetal body volume (FBV) ratio (FLV/FBV-ratio). As controls, we included 33 healthy fetuses. Hepatomegaly was evaluated postmortem in 11 cases of congenital CMV infection. Parametric trend and intraclass correlation analyses were performed. Results: There were no significant differences in FLV between infected (n=32) and healthy fetuses. On correcting the FLV for AC and FBV, we observed a significantly higher FLV in CMV-infected fetuses. There were no significant differences in the FLV, or the FLV/AC or FLV/FBV-ratios according to the severity of brain abnormalities. There was excellent concordance between the fetal liver weight estimated by MRI and liver weight obtained postmortem. Hepatomegaly was not detected in any CMV-infected fetus. Conclusion: In CMV-infected fetuses, FLV corrected for AC and FBV was higher compared to healthy controls, indicating relative hepatomegaly. These parameters could potentially be used as surrogate markers of liver enlargement.